2019
DOI: 10.1158/1078-0432.ccr-19-0191
|View full text |Cite
|
Sign up to set email alerts
|

NRG1 Gene Fusions Are Recurrent, Clinically Actionable Gene Rearrangements in KRAS Wild-Type Pancreatic Ductal Adenocarcinoma

Abstract: Purpose: Gene fusions involving neuregulin 1 (NRG1) have been noted in multiple cancer types and have potential therapeutic implications. Although varying results have been reported in other cancer types, the efficacy of the HER-family kinase inhibitor afatinib in the treatment of NRG1 fusionpositive pancreatic ductal adenocarcinoma is not fully understood. Experimental Design: Forty-seven patients with pancreatic ductal adenocarcinoma received comprehensive wholegenome and transcriptome sequencing and analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
122
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(129 citation statements)
references
References 40 publications
2
122
0
2
Order By: Relevance
“…The ectopic ERBB signalling pathway, including constitutive activation of MEK, ERK, and PI3K, represents a potentially promising target in NRG1 fusion-initiated KRAS wild-type PDAC [85]. The anti-ERBB3 antibody GSK2849330 and pan-ERBB inhibitors afatinib and neratinib impaired cell proliferation in multiple cancer cell lines with NRG1 rearrangements.…”
Section: Gene Fusions As Promising Targets In Kras Wild-type Pdacmentioning
confidence: 99%
“…The ectopic ERBB signalling pathway, including constitutive activation of MEK, ERK, and PI3K, represents a potentially promising target in NRG1 fusion-initiated KRAS wild-type PDAC [85]. The anti-ERBB3 antibody GSK2849330 and pan-ERBB inhibitors afatinib and neratinib impaired cell proliferation in multiple cancer cell lines with NRG1 rearrangements.…”
Section: Gene Fusions As Promising Targets In Kras Wild-type Pdacmentioning
confidence: 99%
“…In addition, some studies have demonstrated the actionability of NRG1 fusions in PDAC. Indeed, when patients affected by heavily pretreated PDAC carrying NRG1 fusion received matched therapy with afatinib, an irreversible ERBB1–4 inhibitor, clinical benefit and objective responses were documented [ 65 , 66 ]. However, Drilon at al recently reported four patients affected by IMA of the lung with NRG1 fusion that did not respond to afatinib, but showed an extraordinary clinical response to treatment with a new monoclonal antibody targeting ERBB3 [ 67 ].…”
Section: Molecular Pathology and Therapeutic Opportunitiesmentioning
confidence: 99%
“…PDAC driver mutations have proven difficult to target in the clinical setting, with the exception of microsatellite instability with immune check point inhibitors [ 17 ] or BRCA1/2 mutations with platinum-based chemotherapies and PARP-inhibitors [ 18 , 19 ]; however, these concern only a small number of patients. KRAS wild-type patients comprise between 5 and 8% of sporadic PDAC patients [ 20 ] and have been shown to harbor actionable genomic alterations [ 21 ], such as NTRK [ 22 ] or NRG1 [ 23 , 24 ] fusions. While molecular subtypes and actionable genomic alterations may theoretically help guide precision medicine approaches, the molecular characterization of PDAC in patients with advanced disease has not yet entered routine clinical practice.…”
Section: Pancreatic Cancer: Clinical Situationmentioning
confidence: 99%